Harmonisation of Islamic Law and National Law in Implementasion of Hajj and Umrah in Indonesia - Aljawi, Muhammad Farid; Hoesein, Zaenal Arifin (CV. Era Digital Nusantara, 2025)
Hajj and umrah are among the main pillars of Islam, and have complex spiritual, social and legal aspects. As the country with the largest number of pilgrims in the world, Indonesia faces many problems in organising the hajj and umrah. In this situation, it is very important to harmonise Islamic law, which serves as the basis for religious norms, with national law, which serves as a tool for the state to protect, provide services and supervise. To investigate the synchronisation between the two legal systems, this study uses a normative juridical approach, employing legislative and conceptual perspectives. The results of the analysis show that although most Sharia principles have been incorporated into national law, particularly Law No. 8 of 2019 on the Implementation of Hajj and Umrah, there are still several problems in their application. Limited quotas for Hajj, mismatched services between regular and special Hajj, and commercial practices that harm pilgrims are some of the main problems. Many previous studies have concentrated on the normative aspects of Islamic law or the administrative aspects of national law, but few have examined both comprehensively. In this article, a model of legal harmonisation based on substantive justice that emphasises legal certainty and the protection of pilgrims' rights is intended to fill this gap. This study has two benefits: theoretically, it offers a conceptual framework for the integration of Islamic law and national law in the implementation of the Hajj and Umrah pilgrimages; and practically, it offers policy recommendations to help the government strengthen Hajj governance that focuses on pilgrim protection. Therefore, this article argues that legal harmonisation is a prudent way to achieve a more equitable, transparent, and substantively just administration of the Hajj and Umrah in Indonesia.